Influence of multiple friction stir welding passes on the microstructure and mechanical properties of AA2024 age-hardened aluminum alloy - Yadav S.K.; Yusufzai M.Z.K.; Mishra S.; Singh D.K. (My University, 2025)
Friction stir welding (FSW) is a promising joining process for age-hardened aluminum alloys. However, when the process is used for welding age-hardened aluminum alloys, the hardness and joint efficiency are poor mainly because the strengthening precipitates become incoherent and/or get dissolved during the welding process. In this novel work, efforts have been made to enable the reprecipitation of the strengthening precipitates using multi-pass FSW. After producing FSW welds on AA2024 alloy, the welds have been processed by the same tool and at the same parameters several times to facilitate the reprecipitation of strengthening precipitates. As the precipitation kinetics of age-hardened aluminum alloys are temperature-dependent, a thermal imaging camera was utilized to record the temperature history during welding and subsequent cooling of the welded plates. The metallurgical examination of welded samples was carried out using optical microscopy, Scanning Electron Microscope (SEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), and microhardness test. It was observed that grain refinement occurs continuously due to dynamic recrystallization and severe plastic deformation up to the third FSW pass, after which there is no significant change in grain size. Generally, the microhardness value was higher in the stir zone than the heat-affected zone (HAZ), and the hardness in the stir zone increased after 4 passes of FSW. SEM images show clusters of incoherent precipitates, fragmentation, precipitate dispersion, dissolution, and reprecipitation of precipitates during each subsequent pass. The identification of the precipitates was carried out using EDS and XRD analysis. © IMechE 2024.